IS6110 Copy Number in Multi-Host Mycobacterium bovis Strains Circulating in Bovine Tuberculosis Endemic French Regions - Charles, Ciriac; Conde, Cyril; Biet, Franck; Boschiroli, Maria Laura; Michelet, Lorraine (Frontiers in Microbiology, 2022)
IS6110 is an insertion sequence found in the Mycobacterium tuberculosis complex, to which Mycobacterium bovis belongs, which can play a role in genome plasticity and in bacterial evolution. In this study, the abundance and location of IS6110 on M. bovis genomic data of French animal field strains were studied. A first analysis was performed on a panel of 81 strains that reflect the national M. bovis population’s genetic diversity. The results show that more than one-third of them are IS6110 multicopy and that 10% have IS6110 in a high copy number (more than 6 copies). Multicopy strains are those circulating in the regions where prevalence was above the national average. Further study of 93 such strains, with an IS6110 copy number of 10-12, showed stability of IS6110 copy number and genome location over time and between host species. The correlation between M. bovis multicopy strains and high bovine tuberculosis (bTB) prevalence leads us to consider whether their epidemiological success could be partly due to genetic changes originated by IS6110 transposition.